Remarks on the Initial and Terminal Value Problem for Time and Space Fractional Diffusion Equation. (4th October 2022) - Nguyen, Hoang Luc
Abstract : The fractional problem for partial differential equation has many applications in science and technology. The main objective of the paper is to investigate the convergence of the mild solution of the diffusion equation with time and space fractional. We consider the problem in two cases which are forward problem and inverse problem. We use new techniques to overcome some of the complex assessments.